2013
DOI: 10.2458/azu_js_rc.55.16102
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Variability in ABA Chemical Pretreatment Close to the 14C Age Limit

Abstract: ABSTRACT. The acid-base-acid (ABA) procedure is a common chemical pretreatment used on most organic matter samples. Although this pretreatment is straightforward, there is no consensus among labs about the optimum strength of the chemicals, or even the temperature, to be used for digestions. Comparisons between 14 C results obtained by samples undergoing ABA against other wet oxidations, such as acid-base oxidation followed by stepped-combustion (ABOX-SC) or -cellulose on wood, have sometimes suggested that A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…However, the typical procedure involves a series of warm acid and alkaline washes, and rinsing with deionized water. Santos and Ormsby (2013) made a compilation of several ABA treatments to evaluate their weaknesses and strengths, and found that most of them are suitable even when 14 C ages are close to the 14 C limit (>50 ka BP). Organic samples that are difficult to clean may require a more aggressive treatment, such as wet oxidation (also termed ABOX, e.g. acid, base, oxidation treatment) with or without the stepped-combustion procedure (Bird et al 1999a; Santos et al 2001; Brock and Higham 2009; Haesaerts et al 2013), stepped-combustion alone (McGeehin et al 2004), or hydropyrolysis (Ascough et al 2010).…”
Section: Conventional Methodological Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the typical procedure involves a series of warm acid and alkaline washes, and rinsing with deionized water. Santos and Ormsby (2013) made a compilation of several ABA treatments to evaluate their weaknesses and strengths, and found that most of them are suitable even when 14 C ages are close to the 14 C limit (>50 ka BP). Organic samples that are difficult to clean may require a more aggressive treatment, such as wet oxidation (also termed ABOX, e.g. acid, base, oxidation treatment) with or without the stepped-combustion procedure (Bird et al 1999a; Santos et al 2001; Brock and Higham 2009; Haesaerts et al 2013), stepped-combustion alone (McGeehin et al 2004), or hydropyrolysis (Ascough et al 2010).…”
Section: Conventional Methodological Techniquesmentioning
confidence: 99%
“…acid, base, oxidation treatment) with or without the stepped-combustion procedure (Bird et al 1999a; Santos et al 2001; Brock and Higham 2009; Haesaerts et al 2013), stepped-combustion alone (McGeehin et al 2004), or hydropyrolysis (Ascough et al 2010). Regardless of the chemical strategy adopted, note that those harsh digestions may require several milligrams of organic material (more than usual); therefore, the risks of the procedure should be evaluated carefully (Higham et al 2009; Santos and Ormsby 2013). ABA pretreatments (as well as holocellulose extractions, Southon and Magana 2010) can be carried out in large batches when using 13×100mm disposable borosilicate glass tubes coupled with heat blocks up to ~200°C maximum.…”
Section: Conventional Methodological Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The classical ABA (acid-base-acid) method described by de Vries and Barendsen (1954) is routinely used in many laboratories for the pretreatment of various organic samples, including wood. Largely modified in the different 14 C laboratories (Santos and Ormsby 2013), this method isolates the wood cellulose and lignin and removes exogenous inorganic and organic carbon. Nevertheless, the ABA treatment can leave behind a residual contamination in very old samples (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid disintegration of the keratinized material under alkaline conditions, this chemical treatment was performed at room temperature. [50] The samples were then dried at 40°C. This pretreatment procedure is designed to remove molecules adsorbed or transferred onto the surface of the keratinized material by endogenous-exogenous pathways.…”
Section: Keratin Protein Conventional Pretreatmentmentioning
confidence: 99%